Cyclic Fatigue Resistance of Five Different Glidepath Files in Double Curved Artificial Canals - Aminsobhani , Mohsen; Meraji, Naghmeh; Azizlou , Elaheh; Sadri, Ehsan (Iranian Endodontic Journal, 2022)
Introduction: The aim of this study was to examine the cyclic fatigue resistances #16 ProGlider, #15.02 Scout RaCe, #15.03 NeoNiti, One G and Path-File NiTi glide path files in S-shaped artificial canals. Materials and Methods: Twenty files from each group were tested. An artificial groove simulating double (S-shaped) curved canal measuring 1.5 mm in width at the top level decreasing towards the apical reaching 0.3 mm at the tip having a 0.06 taper, 18 mm in length, and 1.5 in depth machined in a stainless steel block was used in this study. Resistance to cyclic fatigue was determined by counting the numbers of cycles to failure (NCF). Furthermore, the fragment length of the fractured tips and angle and radius of curvature formed by each file in each trajectory were evaluated. The data were analyzed using the one-way analysis of variance and Tukey’s HSD test and the level of significance was set at 5%. Results: NeoNiti GPS and Scout RaCe glide path files showed significantly higher NCF values compared to other evaluated glide path files (P<0.001) but no significant difference when compared with each other (P=0.67). Conclusion: Based on this in vitro study NeoNiti GPS and Scout RaCe glide path files had the highest cyclic fatigue resistance in simulated double (S-shaped) curved artificial canals among the evaluated path finding files. Therefore, it seems that they can be used with more confidence in endodontic treatment of S-shaped canals clinically.